2000
DOI: 10.1097/00003246-200002000-00020
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of costs of care in mechanically ventilated patients with chronic obstructive pulmonary disease

Abstract: Costs of ICU and non-ICU respiratory care for patients with COPD are higher than costs of care for other mechanically ventilated patients. Although the increased cost of bronchodilators and oximetry in these patients may serve as target areas for reductions in respiratory care costs, it may also be true that these modalities of therapy and management are necessary and need to be used with even greater intensity to achieve better outcomes. The predominant contributions of bed and pharmacy costs in all of our pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 33 publications
3
26
1
Order By: Relevance
“…There was statistically significant difference (p<0.05). We found that the mortality rate was 42.9%, this result was higher than previous studies, [8,9,11,12,14,15] but in our study all of the patients had respiratory failure and had mechanical ventilation.…”
Section: Discussioncontrasting
confidence: 73%
See 4 more Smart Citations
“…There was statistically significant difference (p<0.05). We found that the mortality rate was 42.9%, this result was higher than previous studies, [8,9,11,12,14,15] but in our study all of the patients had respiratory failure and had mechanical ventilation.…”
Section: Discussioncontrasting
confidence: 73%
“…[8][9][10][11][12][13][14][15] Añón et al [8] analysed the prognosis and costs of mechanical ventilation in patients with exacerbations of COPD in an university hospital ICU. They found that the mean age was 64 years (44-77).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations